Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai di Kantor Dinas Perindustrian, Perdagangan, Koperasi Dan UMKM Kab. Toraja Utara - Gilbert Fakambanan; Jens Batara Marewa; Lisa Kurniasari Wibisono (CV. Ulil Albab Corp, 2024)
This research aims to determine the influence of work discipline on employee performance at the North Toraja District Office of Industry, Trade, Cooperatives and MSMEs. This research has a quantitative design and uses a survey method to collect data. The number of samples used in this research was 32 respondents. The data collection procedures for this research are: Questionnaire. Using simple linear regression analysis with SPSS version 25. Hypothesis testing is carried out so that the significance value for the influence of received has an influence on X (Work Discipline) on Y (Employee Performance). The partial results of this research (t test) show that the significance value of work discipline (X) on employee performance is 0.039 < 0.05 and the calculated t value is 2.160 > t table value 2.042. This means that there is a significant influence of work discipline on employee performance, indicating that the work discipline variable has an influence on employee performance at the Department of Industry, Trade, Cooperatives and MSMEs, North Toraja Regency